2001
DOI: 10.1046/j.1523-1755.2001.00073.x
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular mRNAs in human type 1 diabetes: Biochemical evidence for microalbuminuria as a manifestation of diabetic nephropathy

Abstract: To our knowledge, these data provide the first biochemical evidence demonstrating that the glomeruli of microalbuminuric patients and those with overt proteinuria do not differ significantly. The data support the concept that microalbuminuria is not "predictive" of diabetic nephropathy, but rather is an earlier point in the spectrum of diabetic nephropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
1
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 18 publications
4
39
1
1
Order By: Relevance
“…The apparent discrepancy with the similarly elevated kidney mRNA levels in all five microalbuminuric patients and six patients with DN reported by Adler et al (23) might indicate that plasma CTGF level is not solely determined by renal CTGF expression. Moreover, microalbuminuric patients are heterogeneous with respect to progression.…”
Section: Elevated Plasma Ctgf In Diabetic Nephropathycontrasting
confidence: 79%
See 1 more Smart Citation
“…The apparent discrepancy with the similarly elevated kidney mRNA levels in all five microalbuminuric patients and six patients with DN reported by Adler et al (23) might indicate that plasma CTGF level is not solely determined by renal CTGF expression. Moreover, microalbuminuric patients are heterogeneous with respect to progression.…”
Section: Elevated Plasma Ctgf In Diabetic Nephropathycontrasting
confidence: 79%
“…Adler et al (23) found equally elevated CTGF mRNA levels in glomeruli of microalbuminuric (n ϭ 5) and DN (n ϭ 6) diabetic patients. We now add to this notion that CTGF-N levels are elevated in plasma of almost all type 1 diabetic patients with DN and also in about one-third of microalbuminuric patients, but only in a small minority of normoalbuminuric patients.…”
Section: Plasma Ctgf-n Level Correlates With Hba 1cmentioning
confidence: 96%
“…Elevated CTGF levels in glomeruli of NOD mice appear to correlate with the duration of diabetes (89). Elevated CTGF expression was also detected in human DN (89, 162,163). In vitro studies have shown that CTGF is induced in renal cells by both high glucose and AGE (87,89,160), as well as ROS (164), which they generate.…”
Section: Growth Factors and Hormones Affecting Matrix Protein Expressmentioning
confidence: 99%
“…In renal biopsy specimens from patients with diabetes, elevated levels of CTGF mRNA are associated with chronic tubulointerstitial damage, albuminuria, and progression of renal insufficiency (37)(38)(39).…”
mentioning
confidence: 99%